Predicting left ventricular functional recovery in ischaemic cardiomyopathy: needs and challenges. (21st April 2023) - Radesich, Cinzia; Cappelletto, Chiara; Indennidate, Carla; Perotto, Maria; Di Lenarda, Andrea
Abstract: Left ventricular (LV) systolic function is an essential parameter for the evaluation of patients with ischaemic heart disease, and therapeutic choices are significantly driven by LV ejection fraction (LVEF) in the early stage of the disease and during follow-up. After an acute coronary syndrome, ventricular dysfunction may be reversible when caused by transient myocardial stunning. Therefore, the identification of clinical, laboratory, and instrumental predictors of improvement in LV systolic function (in addition to LVEF) is essential for an adequate prognostic stratification. In the setting of chronic ischaemic heart disease, there is no evidence that an improvement in LV systolic function is invariably associated with a better prognosis and LVEF is only one of many parameters that should be considered for the risk stratification. This state-of-the-art review will critically analyse the scientific evidence regarding known predictors of LVEF recovery, trying to elucidate their pathophysiological principles and clinical value.